Solid Waste Management: A Critique of Nigeria’s Waste Management Policy - Samuel Ebie (The International Journal of Knowledge, Culture, and Change Management: Annual Review, 2012)
Solid waste management is the application of techniques that will ensure the orderly execution of the functions of collection, transfer, processing, treatment and disposal of solid waste. The ever increasing global concern on environmental health demands that wastes be properly managed and disposed of in the most friendly and acceptable way. This is to minimise, and were possible, eliminate its potential harm to humans, plants, animals and natural resources. Solid waste has become an important issue in Nigerian. Piles of wastes are often found by roads, rivers and many other open spaces in the cities, and this is causing significant health and environmental problems. The discovery of a major toxic waste dumped by a foreign company at Koko town near Warri in Delta State, Nigeria in 1987 led to the establishment of the Federal Environmental Protection Agency (FEPA) by Decree No. 58 of 1988. FEPA regulates the collection, treatment and disposal of solid and hazardous waste from municipal and industrial sources, and makes Environmental Impact Assessment (EIA) mandatory for any major development project likely to have adverse impact on the environment. FEPA Act has been repealed and replaced with National Environmental Standards and Regulations Enforcement Agency. This study presents a critique of the current solid waste management practices, policies and laws in Nigeria. Primary and secondary data were gathered by sending semi-structured questionnaire to key informant persons and dump site visit. Content analysis was utilized especially for the secondary data since bulk of the data come from secondary material. It is evident that solid waste management in Nigeria is plagued with inefficient collection methods, insufficient coverage of the collection system, improper disposal, lack of institutional arrangement, insufficient financial resources, absence of bylaws and standards, inappropriate technology, etc. While the policies and laws are fragmented and are formulated not on nationally generated baseline data, participation of the people in the policy formulation and implementation is lacking, enforcement and monitoring of laws and policies is inadequate. It is therefore necessary that the legal (policies and laws), institutional, political, socio-cultural, financial, economic and technical aspects of solid waste management be given optimum attention with all seriousness.Suresh S. Surendran